Sensorless control of synchronous motor drive with forced dynamics - Ján Vittek; Slavomír Seman; Daniel Vaňko (Communications - Scientific letters of the University of Zilina, 1999)
Acontrol method for electric drives employing synchronous motors with forced closed-loop dynamics is presented. The prescribed response to the reference speed demand can be chosen as direct acceleration control, linear first order and second order speed response. In addition to this, the angle between the stator current and magnetic flux vectors can be mutually maintained perpendicular. The drive control system also contains a set of two observers for estimation of rotor speed and the load torque. The experimental results obtained for direct acceleration, first order dynamic and second order dynamic indicate good agreement with the theoretical. The control system, as developed to date, would be suited very well to applications requiring control to a moderate accuracy.